High stability perovskite solar cells under ambient conditions - Aslan, Emre; Ates Turkmen, Tulin; Alturk, Elif (INST ENGINEERING TECHNOLOGY-IET, 2020)
Though perovskite solar cells have outstanding commercialisation potential, perovskite materials are very vulnerable to moisture and oxygen. So the main issue for perovskite solar cell is very fast degradation. In order to elaborate on this concern, the stability of perovskite solar cells were investigated in this study. The effect of oxygen and moisture on perovskite solar cells decreased with encapsulation of the cells. Encapsulation has been carried out with ultraviolet cured epoxy resin. Stability tests were taken place in laboratory conditions under solar simulator and also shelf-life tests. Perovskite solar cells showed the highest power conversion efficiency (PCE) of 9.77% with a short circuit current density of 22.5 mA/cm(2), the open-circuit voltage of 0.94 V and fill factor of 0.46. After 2800 h, perovskite solar cells were still 85% stable in atmospheric conditions. Perovskite solar cells exhibited distinctive durability for shelf-life test in laboratory conditions. The PCE of perovskite solar cells were decreased only 15% of its initial value after 2800 h. In order to elaborate the degradation of perovskite solar cells, the cells are exposed to solar irradiation AM1.5G. Perovskite solar cells degraded gradually with time under solar irradiation; however, this stability test indicated that the solar cells were durable 20% after 500 h exposure to solar irradiation.
Keywords: short-circuit currents; solar cells; current density; durability; life testing; curing; photovoltaic power systems; mechanical stability; resins; oxygen; encapsulation; laboratory techniques; power conversion; reliability; mechanical testing; solar irradiation; high stability perovskite solar cell; ambient conditions; oxygen effects; moisture effects; ultraviolet cured epoxy resin; stability tests; laboratory conditions; high power conversion efficiency; short circuit current density; shelf-life tests; open-circuit voltage; fill factor; atmospheric conditions; solar cells degradation; time 500; 0 hour; voltage 0; 94 V; time 2800; PERFORMANCE; DEGRADATION; EFFICIENCY; Science & Technology - Other Topics; Energy & Fuels; Engineering